2011
DOI: 10.1590/s0103-90162011000400003
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of salt-affected soil by the addition of organic matter: an investigation into improving glutinous rice productivity

Abstract: Soil salinity may limit plant growth and development, and cause yield loss in crop species. This study aimed at remediating saline soil using organic matter (OM) treatment, before the cultivation of RD6 rice (Oryza sativa L. spp. indica). Physiological and morphological characters of rice plants, as well as crop yield, were evaluated from salt-affected soil with varying levels of salinity. The chlorophyll a and total chlorophyll pigments of rice plants grown in salt-affected soil (2% salt level) with the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 28 publications
(36 reference statements)
3
25
0
1
Order By: Relevance
“…The most serious cause of yield reduction in crops grown in saline paddy fields that have not undergone remediation are the subsequent effects of toxic ion accumulation in the plant cell, which causes pigment reduction, diminishes chlorophyll a and lowers A (Cha-um and Kirdmanee, 2011). However, in the present study A was effectively alleviated with 6% OM in soil in treatments with excess of B and with salt alone (Figure 1), similar to the control plants.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The most serious cause of yield reduction in crops grown in saline paddy fields that have not undergone remediation are the subsequent effects of toxic ion accumulation in the plant cell, which causes pigment reduction, diminishes chlorophyll a and lowers A (Cha-um and Kirdmanee, 2011). However, in the present study A was effectively alleviated with 6% OM in soil in treatments with excess of B and with salt alone (Figure 1), similar to the control plants.…”
Section: Discussionsupporting
confidence: 55%
“…In Hordeum maritimum and rice cv. RD6 total chlorophyll pigment levels were also maintained better with the application of OM (Lakhdar et al, 2008;Cha-um and Kirdmanee, 2011). Organic matter may contain salt ion-binding agents which detoxify the toxic ions, especially Na + and Cl -, as indicated by low EC in treated soil (Tejada et al, 2006;Zahid and Niazi, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the case of bean seeds, Neves et al (2008) observed that irrigation with saline water (ECw 5.0 dS m -1 ) started after germination and until the end of the bean cycle it did not influence the weight of 100 seeds. This increase in weight of 100 seeds and seed mass can be attributed to the beneficial action of bovine biofertilizer, as the organic feedstock operates in the physical improvement of the soil for root growth systems, as discussed by Mgbeze and Abu (2010) and Benbouali et al (2013) and also to improve soil biological activity (Cha-Um and Kirdmanee, 2011).…”
Section: Resultsmentioning
confidence: 93%
“…In this sense, according to Cha-um and Kirdmanee (2011), the organic compost from castor beans in soils degraded by salts stimulates growth, biomass production and physiological efficiency of plants in saline environments. Changes in metabolism induced by salinity are the result of plants' physiological responses such as: Stimulus to growth, photosynthetic capacity, and accumulation of chlorophyll .…”
mentioning
confidence: 99%